ORGANIC BREAD WITH HEMP BY-PRODUCTS: REGULATORY REQUIREMENTS AND QUALITY - FALENDYSH, NATALIIA; BLAZHENKO, MARIIA; BOBEL, INNA; KAMBULOVA, YULIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Organic products, and accordingly organic production, due to the absence of harmful chemicals and a higher content of nutrients, can positively affect human health, contributing to better well-being and reducing the risk of chronic diseases. Organic farming and production of organic products also supports ecology and biodiversity, which contributes to sustainable development. By choosing organic products, consumers contribute to their own health, as well as to the health of the nation and the environment.Food is a source of energy and nutrients for humans. They provide the body with the necessary macro- and microelements that are needed for growth, development, maintenance of vital activity and physical activity. Enrichment of food products, in particular bakery products, with biologically valuable plant raw materials will increase their nutritional value and provide health-improving properties.The work investigated the quality indicators and nutritional value of organic bread made from high-quality wheat flour, the recipe of which includes products from hemp seeds. Hemp products, namely hemp flour and hemp protein, are rich in macro- and microelements that are necessary for the normal functioning of the human body. Studies have shown that adding hemp seed products to bread made from wheat flour improves its nutritional value and increases the daily human need for proteins, essential amino acids, dietary fiber and minerals. Thus, the daily need (its coverage) for proteins increases by 17-18%, for fats - by 3.0-6.2%, for dietary fiber - by 5.0-12.5%.Products with the addition of hemp protein retain freshness better, which is confirmed by the degree of freshness preservation.Bread using hemp products contains more aromatic compounds compared to the control sample.
Keywords: оrganic products; bread; nutritional value; protein; minerals